Growth cycles in Argentina: the recent behavior - Perrotti, Daniel E. (2021)
This article presents a characterization of Argentina’s gross domestic product (GDP) cycles of the last four decades. The extraction strategy follows two well-known approaches: the classic and the growth cycle. Both approaches show related results in terms of the number of cycles; cycles’ duration; the prevalence of expansions to contractions’ duration; cycles’ dating; and, the intensity of the different phases. The selection criteria used in the literature allowed the Christiano and Fitzgerald (CF) filter to stand out with desirable characteristics for Argentina’s GDP series over the rest of the alternatives considered in the growth cycle analysis.